Use Media Learning For Improving Student Learning Outcomes In Secondary Schools - Reno Renaldi (Jurnal Ilmu Pendidikan dan Humaniora, 2025)
Learning media is an instrument used by educators in the learning process to create an interesting learning atmosphere and facilitate understanding in accordance with the learning objectives that have been set. There are various types of learning media that can be utilized, both those sourced from the surrounding environment and industrial production results. This article aims to examine the use of effective learning media in an effort to improve student learning achievement at the secondary school level. This study uses a qualitative approach with a literature review method. Data collection was carried out through documentatio. There are no sources in the current document.n techniques from various relevant sources, such as scientific articles and books, then analyzed using content analysis techniques. The results of the study showed that the use of learning media had a significant effect on improving student learning outcomes, with various benefits including making learning more interesting and making it easier for students to understand the material